Przepis na reporterski serial prasowy - Listoś, Agata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
The article presents the characteristic features of a distinct journalistic genre, which is press reporting series, based on Gazeta Wyborcza’s publishing Afganistan – polska wojna za górami, Brat Karol, siostra Wanda and Na szlaku kuriera z Warszawy. The present author tries to find the characteristics of this genre by describing the character category, the time and space category, the progress of cause and effect between episodes and the periodicity of the featured components.